Cryotherapy for Prevention of Taxane-Induced Peripheral Neuropathy: A Meta-Analysis - Jia, Junting; Guo, Yimeng; Sundar, Raghav; Bandla, Aishwarya; Hao, Zhiying (Frontiers in Oncology, 2021)
Purpose Taxanes are widely used in gynecological cancer therapy, however, taxane-induced peripheral neuropathy (TIPN) limits chemotherapy dose and reduces patients' quality of life. As a safe and convenient intervention, cryotherapy has been recommended as a promising intervention in the recent clinical guidelines for the prevention of TIPN. Although there are a considerable number of studies which explored the use of cryotherapy in preventing CIPN, there is insufficient large-scale clinical evidence. We performed a meta-analysis on the current available evidence to examine whether cryotherapy can prevent TIPN in cancer patients receiving taxanes. Methods We searched databases including PubMed, Embase, and Cochrane from inception to August 3, 2021 for eligible trials. Clinical trials that examined the efficacy of cryotherapy for prevention of TIPN were included. The primary outcome was the incidence of TIPN, and secondary outcomes were incidence of taxane dose reduction and changes in nerve conduction studies. The meta-analysis software (RevMan 5.3) was used to analyze the data. Results We analyzed 2250 patients from 9 trials. Assessments using the Common Terminology Criteria for Adverse Events (CTCAE) score showed that cryotherapy could significantly reduce the incidence of motor and sensory neuropathy of grade≥2 (sensory: RR 0.65, 95%CI 0.56 to 0.75, p<0.00001; motor: RR 0.18, 95% CI [0.03, 0.94], p=0.04). When evaluated using the Patient Neuropathy Questionnaire (PNQ), cryotherapy demonstrated significant reduction in the incidence of sensory neuropathy (RR 0.11, 95% CI 0.04 to 0.31], p<0.0001), but did not show significant reduction in the incidence of motor neuropathy (RR 0.46, 95% CI 0.11 to 1.88, p=0.28). Cryotherapy was associated with reduced incidences of taxane dose reduction due to TIPN (RR 0.48, 95% CI [0.24, 0.95], p=0.04) and had potential to preserve motor nerves. Conclusions Cryotherapy is likely to prevent TIPN in patients receiving taxanes. High quality and sufficient amount of evidence is warranted.